"We Should Not Regard AM as a Stand‐Alone Technology": Interview with Carsten Merklein, head of the additive manufacturing department at Schaeffler Technologies. Issue 4 (24th October 2018) - Unknown
Abstract: As a global automotive and industry supplier, the Schaeffler Group offers a broad portfolio of motor, drive, and chassis components, as well as rolling and plain bearing solutions. Carsten Merklein is head of the additive manufacturing department in the area of tool management and prototypes at Schaeffler Technologies in Herzogenaurach. Since April 2018, he is board member of the Additive Manufacturing association within VDMA.